2004
DOI: 10.1088/1126-6708/2004/11/016
|View full text |Cite
|
Sign up to set email alerts
|

A strategy to study the role of the charm quark in explaining the Delta{I}=1/2 rule

Abstract: We present a strategy designed to separate several possible origins of the well-known enhancement of the ∆I = 1/2 amplitude in non-leptonic kaon decays. In particular, we seek to unambiguously quantify the rôle of the charm quark mass in the observed enhancement. This is achieved by considering QCD with an unphysically light charm quark, so that the theory possesses an approximate SU(4) L × SU(4) R chiral symmetry. The strategy proceeds by computing the relevant operator matrix elements and monitoring their va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(138 citation statements)
references
References 90 publications
2
135
0
1
Order By: Relevance
“…It turns out [20], however, that in the normalised observable [C 27 ] ab norm (x 0 , y 0 ) that we have considered here, the contributions from the Goldstone zeromodes cancel out at this order. Therefore the result can in fact formally be expanded as a Taylor-series in (M L) 2 , with the zeroth order term agreeing with the result of the ǫ-regime (see below).…”
Section: P-regimementioning
confidence: 83%
See 2 more Smart Citations
“…It turns out [20], however, that in the normalised observable [C 27 ] ab norm (x 0 , y 0 ) that we have considered here, the contributions from the Goldstone zeromodes cancel out at this order. Therefore the result can in fact formally be expanded as a Taylor-series in (M L) 2 , with the zeroth order term agreeing with the result of the ǫ-regime (see below).…”
Section: P-regimementioning
confidence: 83%
“…Considering, in particular, the operators 20) which appear in the computations of Fig. 2, and choosing the indices that appear in the physical operators O 27 and O 8 , we obtain …”
Section: Appendix a Irreducible Representations Of The Valence Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section the propagator techniques are applied to an ongoing project to study the role of the charm quark in the explanation of the ∆I = 1/2 rule [18,19,20]. Our physics results are presented in a companion paper [21]; preliminary results from this study have also been reported in Ref.…”
Section: Eye Diagrams For K → πmentioning
confidence: 99%
“…This procedure complements for the case of the chiral condensate the low-mode averaging (LMA) technique proposed in ref. [49]. The latter has been successfully applied already to meson two-point functions [49 -51], baryon two-point functions [52] and more recently to three-point functions for the extraction of low-energy constants of the ∆S = 1 chiral effective Hamiltonian [53].…”
Section: Numerical Estimatormentioning
confidence: 99%